Pelatihan Dan Pendampingan Pembuatan Media Pembelajaran Audio Visual Berbasis Aplikasi Canva SD Negeri Sepring - Anna Maria Oktiviani; Avi Valentri; Hilda Dhaniartika Nurma’ardi (MULIA (Jurnal Pengabdian kepada Masyarakat), 2024)
Canva is a platform used for designing and can be accessed via websites and mobile applications. Canva is designed with complete features and templates that make it easy for someone to design things such as posters, greeting cards, brochures, infographics and presentations in a short time. Activities carried out at the Sepring State Elementary School in Serang City include providing workshops/training to teachers. The method used in this activity is training and mentoring in learning media using Canva combined with the Important Performance Analysis (IPA) method for teachers at the Sepring State Elementary School. The evaluation results show that the teachers as training participants have made active efforts to understand the concept and implementation of using the Canva application in learning media. . The response from participants in making learning media using Canva for all evaluation components was very positive. Based on the results of training in creating interesting learning media using Canva to optimize learning for teachers at the Sepring State Elementary School, it was concluded that the training could increase teacher understanding and teachers' abilities in creating learning media.